Víceúrovňové hodnocení křehkosti vybraných stavebních kompozitů - Machačová, Denisa (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Zadaným tématem diplomové práce je víceúrovňové hodnocení křehkosti stavebních kompozitů. Práce se zabývá posudky lomových parametrů zkušebních těles z lehkého a obyčejného betonu. Zmíněná tělesa se dále odlišovala obsahem vláken v betonových směsích, jejich druhem a délkou. Práce se člení na dvě části, teoretickou a praktickou. Teoretická část pojímá kompozitní materiály a úvod do lomové mechaniky. V praktické části jsou popsány jednotlivé kroky pro získání lomově-mechanických parametrů pomocí programu StiCrack a Excel Visual Basic. Stěžejní částí práce je vyhodnocení křehkosti rozdílných zkušebních vzorků zohledňující druh betonové směsi a druh vláken.

Specified topic of the thesis is a multilevel evaluation of brittleness of selected building composites. The work deals with the opinions of fracture parameters of test specimens of lightweight and ordinary concrete. Specimens further differed fibres content in concrete mixtures, their type and length. The work is divided into two parts, theoretical and practical. The theoretical part conceives composite materials and introduction to fracture mechanics. The practical part describes the different steps for fracture-mechanical parameters evaluation using StiCrack and Excel Visual Basic software. The main part of the work is to evaluate the brittleness of different test specimens, taking into account the type of concrete mix and type of fibres.
Complex evaluation of brittleness of selected building composites
Keywords: obyčejný beton; lehký beton; iniciace lomu; křehkost; posun; rozevření trhliny (CMOD); lomová houževnatost; lomová energie; lomová práce; iniciace trhliny; ordinary concrete; lightweight concrete; fracture initiation; brittleness; deformation; crack mouth opening displacement; fracture toughness; fracture energy; fracture work; crack initiation